The Vertical Residence Based on Biophilic Architectural Design Concept (Case Study: Taman Anggrek Residence Apartment West Jakarta) - Susanto, Fahmi Adhitya Citra; Siwi, Samsu Hendra; Fatimah, Titin (Fakultas Teknik Universitas Pancasila, 2025)
Vertical housing represents a viable and effective option for residential solutions. Various efforts have been made to reintegrate the relationship between humans and the buildings they inhabit. Biophilic design represents a contemporary approach to reconnecting organic life with constructed spaces. This study aims to explore the architectural strategy of biophilic design as a solution to housing needs, focusing on integrating natural elements into living spaces to create a comfortable environment for residents. The investigation utilizes qualitative approaches, incorporating observation and data gathering, to discern the biophilic requirements of apartment inhabitants. The framework of 14 patterns of biophilic design, aimed at improving health and well-being within built environments, acts as a standard for evaluating the implementation of these patterns. The objective is to implement biophilic design in communal living spaces, considering the users of the building, the functions of the spaces, and utilizing knowledge, experience, and user requirements as a foundation for evaluation.